2017
DOI: 10.1016/j.expneurol.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase-4 inhibition restored hippocampal long term potentiation after primary blast

Abstract: Due to recent military conflicts and terrorist attacks, blast-induced traumatic brain injury (bTBI) presents a health concern for military and civilian personnel alike. Although secondary blast (penetrating injury) and tertiary blast (inertia-driven brain deformation) are known to be injurious, the effects of primary blast caused by the supersonic shock wave interacting with the skull and brain remain debated. Our group previously reported that in vitro primary blast exposure reduced long-term potentiation (LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 90 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…Inhibition of PDE4 is considered a potential target for the treatment of nervous system diseases. Several studies have shown that the inhibition of PDE4 can improve hippocampus long-term potentiation (LTP) and dendritic spine density by activating cAMP/protein kinase A (PKA)/cAMP response element binding protein (CREB)/brain-derived neurotrophic factor (BDNF) signaling, increase synaptic plasticity, and then improve cognitive function [ 7 , 8 , 9 ]. For example, inhibition of PDE4 by the first-generation inhibitor Rolipram increased the level of cAMP and p-CREB in the hippocampus, as well as the survival and proliferation of new neurons in the hippocampal dentate gyrus, significantly improving hippocampal long-term potentiation [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of PDE4 is considered a potential target for the treatment of nervous system diseases. Several studies have shown that the inhibition of PDE4 can improve hippocampus long-term potentiation (LTP) and dendritic spine density by activating cAMP/protein kinase A (PKA)/cAMP response element binding protein (CREB)/brain-derived neurotrophic factor (BDNF) signaling, increase synaptic plasticity, and then improve cognitive function [ 7 , 8 , 9 ]. For example, inhibition of PDE4 by the first-generation inhibitor Rolipram increased the level of cAMP and p-CREB in the hippocampus, as well as the survival and proliferation of new neurons in the hippocampal dentate gyrus, significantly improving hippocampal long-term potentiation [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the CNS, PDE4 plays a key role in both chronic neurodegenerative diseases and acute neurological insults, including stroke 14 , 15 . Recently, an increasing number of reports have shown that inhibition of PDE4 is beneficial for neuroplasticity 16 - 18 , making it a promising candidate target that has therapeutic potential for the recovery of stroke. Thus, this review provides a perspective for advancing our understanding of the role of PDE4 in neuroplasticity after stroke, supporting the possibility of exploiting PDE4 inhibitors as effective therapeutics against ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…more dendrites and synapses) by inhibiting the degradation of cAMP. This positive effect of PDE4 inhibition on plasticity has been shown in two different brain injury models and one study actually demonstrated the effect with roflumilast (12,13).…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 62%